Contribution to the Identification of the Professional Skills Profile of Coaches in the Algerian Sport Judo System - Belkadi, Adel; Benbernou, Othman; Sebbane, Mohamed (www.altorendimiento.com, 2015)
This study was designed to determine the professional skills of coaches, which are identified and judged based on a large number of factors. The purpose of this article is to describe the views of four groups of professional actors concerning coaches’ skills: athletes, coaches, leaders and experts from the Algerian judo sport system. The actors of the system responded to the same series of questions regarding coaches’ skills. The actors’ views across the five groups of specific professional skills are more similar than dissimilar, with each professional group emphasizing a different item of the coaches’ skills. The results show that coaches and athletes have the same representations of technical and teaching skills. However, there is a discrepancy in representations regarding organizational and managerial skills. Stakeholders’ views are compared to the coaching science literature, and recommendations for developing a professional skills repository of judo coaches are provided.
Keywords: Identification, Professional Skills, Profile, Coaches